Allocation of Public Expenditure: Some Realities for Development Planning in Bangladesh - Khan, Adil Mohammed (Journal of Bangladesh Institute of Planners, 2014)
Allocation of ‘Public Expenditure’ is very important for a developing country like Bangladesh, where development growth has not taken place in a homogenous way across the country and the regional divide in terms of development is quite significant as well. This paper attempts to analyze the public expenditure pattern of Bangladesh, especially in the distribution of Budget and to analyze the spatial disparity in public expenditure within different regions of Bangladesh. Data on sectoral allocation of national budget as well as the regional pattern of distribution of budget have been analyzed in this paper. Location Quotient (LQ) Analysis, Gini Index, Kuznets Ratio are used for measuring regional variation in budget distribution across the country. This paper reveals that, the western divisions of Barisal, Khulna and Rajshahi divisions should be given special attentions in the distribution of Budget to ensure ‘fair’ share of budgets for development programmes as these regions are quite lagging behind in terms of allocation of budget. Special programs relating to poverty reduction in the forms of social safety net distribution may be increased to the districts of these divisions for reducing the development gap within the country. Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 17-31